Socio-Economic Impact Assessment of Investments framed by the European Union: the case of Portuguese North and Algarve Regions - Emília Malcata Rebelo (2011)
The main goal of the research reported in this article consists of developing a methodology for the assessment of socio-economic impacts of investments framed by European Union programmes. This methodology will support the computation, comparison, and ordering of the impacts of investments on the performance of regional economies, and on populations´ well-being. It will also launch strategic planning and management proposals concerning public investments, focused on the promotion of economic competitiveness and social cohesion. It is applied, as case studies, to the regional European programmes Operação Norte and Proalgarve that took place between 2000 and 2006. This methodology founds on the joint use of methods of multivariate data analysis (cross-section application of factorial analysis and analysis of data tables), auto-regressive vectors (analysis of temporal series) and geographic information systems (spatial analysis). The proposed methodology of socio-economic impact assessment of investments is innovative when compared with current methodologies because it enables: (i) the evaluation and computation of aggregated investments that focus on their effects on regional economic performance and on communities´ well-being; (ii) the objective analysis and computation of the effects of investments in relation to the flat-scenery of their absence, and in relation to comparable investments elsewhere; (iii) the better identification of the causality relations between interventions and results (that shapes an important qualitative jump that goes far beyond the simple comparison of indicators); (iv) to develop the spatial side of the analysis; (v) to strengthen knowledge and experience on most successful investments in each place, according to their specific features; (vi) to anticipate the consequences of certain kinds of investments, what leads to their better operationalization, considering the goals of economic performance and social well-being. This analysis is intended to be a contribution to the required reformulation of the European cohesion policy, and to the definition of investment strategies and policies, pointing them to the regions and places that have managed to reach better results.